Moderasi Beragama dalam Tafsir Sufistik dan Relevansinya dengan Konsep Moderasi Beragama Kementerian Agama RI - Fitri, Muhammad; Nurhadi, Nurhadi (Lembaga Yasin AlSys, 2025)
This study aims to explore the theological foundations of religious moderation through a Sufi exegetical approach and examine its relevance to the concept of religious moderation as formulated by Indonesia’s Ministry of Religious Affairs. The study analyzes three major works of Qur’anic exegesis: Ruh al-Ma‘ani fi Tafsir al-Qur’an al-‘Azim wa al-Sab‘i al-Matsani by Shihab al-Din al-Sayyid Mahmud al-Alusi (1217–1270 H), Lata’if al-Isharat by ‘Abd al-Karim ibn Hawazin al-Qushayri (d. 465 H), and Tafsir al-Azhar by Abdul Malik Karim Amrullah (Hamka, 1908–1981). The analysis focuses on three verses that reflect core values of moderation: QS. Al-Baqarah [2]:143, QS. Yunus [10]:99, and QS. Al-Nahl [16]:125. This research employs a qualitative method using a descriptive-analytical approach within the framework of library research. The findings indicate that all three exegetical interpretations—classical and modern—provide a robust theological basis for promoting religious moderation. They unanimously reject extremism and violence in the name of religion, emphasize balance in thought and practice, and uphold freedom of belief and the right to choose one’s faith. Furthermore, the exegetes advocate for a wise, educational, and culturally accommodating approach to religious propagation. These interpretations align closely with the framework of religious moderation proposed by the Ministry of Religious Affairs, which promotes peaceful religiosity, Islam as a mercy to all creation (rahmatan lil ‘alamin), and a strong commitment to the Republic of Indonesia (NKRI) and Pancasila as national consensus.